HpaR, the Repressor of Aromatic Compound Metabolism, Positively Regulates the Expression of T6SS4 to Resist Oxidative Stress in Yersinia pseudotuberculosis - Wang, Zhuo; Wang, Tietao; Cui, Rui; Zhang, Zhenxing; Chen, Keqi; Li, Mengyun; Hua, Yueyue; Gu, Huawei; Xu, Lei; Wang, Yao; Yang, Yantao; Shen, Xihui (Frontiers in Microbiology, 2020)
HpaR, a MarR family transcriptional regulator, was first identified in Escherichia coli W for its regulation of the hpa-meta operon. Little else is known regarding its functionality. Here, we report that in Yersinia pseudotuberculosis, HpaR negatively regulates the hpa-meta operon similar to in Escherichia coli W. To investigate additional functions of HpaR, RNA sequencing was performed for both the wild-type and the ΔhpaR mutant, which revealed that the type VI secretion system (T6SS) was positively regulated by HpaR. T6SS4 is important for bacteria resisting environmental stress, especially oxidative stress. We demonstrate that HpaR facilitates bacteria resist oxidative stress by upregulating the expression of T6SS4 in Y. pseudotuberculosis. HpaR is also involved in biofilm formation, antibiotic resistance, adhesion to eukaryotic cells, and virulence in mice. These results greatly expand our knowledge of the functionality of HpaR and reveal a new pathway that regulates T6SS4.